2020
DOI: 10.1101/2020.05.08.20095117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation Between Chest Computed Tomography and Lung Ultrasonography in Patients With Coronavirus Disease 2019 (Covid-19)

Abstract: INTRODUCTION: There is growing evidence regarding the imaging findings of Coronavirus Disease 2019 (COVID-19), in chest X-ray and Computed Tomography scan (CT). At this moment, the role of Lung Ultrasonography (LUS) has yet to be explored. OBJECTIVES: The main purpose of this study is to evaluate the correlation between LUS findings and chest CT in confirmed (positive RT-PCR) or clinically highly suspicious (dyspnea, fever, myasthenia, gastrointestinal symptoms, dry cough, ageusia or anosmia) of COVID-19 pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
0
8
0
1
Order By: Relevance
“…But others reported relatively low sensitivity (0.69 and 0.78) for mild and moderate cases of COVID-19 [68]. Similar accuracy of LUS and CT was reported in [47], with LUS identifying signs of COVID-19 more likely than CT (78% vs. 72%). This has caused a vivid debate on the role of LUS for the COVID-19 pandemic [48], [49], [69].…”
Section: Studies Evaluating Ct X-ray and Lusmentioning
confidence: 61%
See 2 more Smart Citations
“…But others reported relatively low sensitivity (0.69 and 0.78) for mild and moderate cases of COVID-19 [68]. Similar accuracy of LUS and CT was reported in [47], with LUS identifying signs of COVID-19 more likely than CT (78% vs. 72%). This has caused a vivid debate on the role of LUS for the COVID-19 pandemic [48], [49], [69].…”
Section: Studies Evaluating Ct X-ray and Lusmentioning
confidence: 61%
“…US has received little attention in AI despite its wide, global availability which is a key factor for dealing pandemics, especially in remote and undeveloped areas where supply chains are long, and repurposing of existing technologies is the sharpest weapon for prompt pandemic alleviation. Given that LUS is also more sensitive than CXR [44], comparable to CT [47], and has evident practical advantages, it is presumably the modality with the highest improvement potential for medical image analysis in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 LUS specificity may therefore be underestimated in studies where LUS is compared only to RT-PCR. For example, in the work by Bar et al 37 specificity was 62% (vs. RT-PCR) but in Tung-Chen et al 31 specificity was 79% (vs. CT).…”
Section: Comparison Of Lus To a Reference Standardmentioning
confidence: 91%
“…In a single centre study by Tung-Chen et al, 31 51 adults presented to ED with confirmed or suspected COVID-19, both received CT and LUS and 67% were admitted. LUS was performed by a single, experienced operator blinded to CT and clinical findings.…”
Section: Comparison Of Lus To a Reference Standard (Ct)mentioning
confidence: 99%